Single Center Experience with Endovascular Repair of Acute Thoracoabdominal Aortic Aneurysms - Katsargyris, Athanasios (Cardiovasc Intervent Radiol, 2021)
PURPOSE: To investigate feasibility and outcomes of endovascular repair for acute thoracoabdominal aortic aneurysms (TAAA). MATERIALS AND METHODS: Data from a single center were retrospectively analyzed. Patients who underwent endovascular repair for acute TAAA between January 2010 and April 2020 were included. Perioperative and mid-term follow-up outcomes were analyzed. Survival, freedom from reintervention, and target vessel patency were calculated by Kaplan–Meier analysis. RESULTS: A total of 30 patients (18 men, 67.5 ± 6.9 years) underwent endovascular repair for acute symptomatic (n = 15) or contained ruptured (n = 15) TAAA. An off-the-shelf four-branched stent-graft (T-Branch) was used in 19 (63.3%) patients, a custom-made device (CMD) with expedite order in 5 (16.7%) patients, a CMD with short anticipated delivery time in 3 (10.0%) patients, and a CMD available in the hospital in 3 (10.0%) patients. Technical success was 90.0% (n = 27). Thirty-day mortality was 10% (n = 3). There was no complete persistent paraplegia, but one (3.3%) patient suffered permanent limb weakness. Estimated survival at 1 and 2 years was 86.3% ± 6.4%, and 82.3% ± 7.2%, respectively. Estimated freedom from reintervention at 1 and 2 years was 81.4% ± 7.6% and 73% ± 8.8%. Estimated target vessel patency at 1 and 2 years was 96.6% ± 2% and 92.6% ± 2.9%. CONCLUSION: Endovascular treatment of acute TAAA in this selected group of patients was associated with low early mortality and excellent mid-term survival. The off-the-shelf stent-graft option (T-Branch) was used in the majority of patients. Endovascular repair should be considered the first option for suitable acute TAAA.